A combination of chicken embryo extract and a nutritional supplement protect a rat model of aging against d-galactose-induced dysfunction of mitochondria and autophagy. Issue 5 (3rd May 2019) - Zhou, Huimin; Ma, Jia; Shan, Yujia; Qi, Xia; Wang, Huaxin; Jia, Li
Abstract : The aging process is usually associated with increased oxidative stress and deficiency of tissues and organs, which causes a decline in the life quality of individuals. Abstract : The aging process is usually associated with increased oxidative stress and deficiency of tissues and organs, which causes a decline in the life quality of individuals. Some anti-oxidant factors derived from foods have been implicated in delaying senescence and sustaining health. The present study aimed to assess the anti-aging effects and underlying mechanism of the combined application of chicken embryo (CE) extract and a nutritional mixture (NM) of 52 ingredients on the aging process ofd -galactose (d -gal)-induced rats. After 90 days of treatment, we observed that CE plus NM administration significantly improved the body weight, visceral indices and histological damage of aging rats. The use of CE or NM alone exhibited similar effects, but was not as effective as the combined use of CE and NM. In addition, the additional nutrients promoted the mitochondrial function ofd -galactose-induced rats. With CE + NM supplementation, cells from senescent rats showed decreased accumulation of reactive oxygen species (ROS), increased levels of mitochondrial membrane potential, elevated numbers of mitochondria, and morphological changes towards normalization compared to the un-treated group. Furthermore, autophagosomes and autophagy-related proteins were up-regulated in aging rats upon exposure to CE + NM. Interestingly, we also found that the protein extracts of CE have similar effects to CE. These results indicate the critical role played by CE + NM in promoting the function of mitochondria and autophagy, therefore regulating the aging process in rats. Our study provides a novel compound design of nutritional support to achieve an optimal nutritional status for anti-oxidation and slowing of aging.